New records of bivalve from Peruvian Sea - Paredes, Carlos (2003)
Six bivalve species: Thyasira flexuosa (Montagu, 1803); Diplodontina tumbesiana Stempell, 1899; Retrotapes exalbidus (Dillwyn, 1817); Pandora (Pandorella) cornuta C.B. Adams, 1852; Entodesma cuneatum (Gray, 1828); Periploma (Cricoploma) carpenteri Dall, 1896 are the first time reported for Peruvian sea. Distribution, habitat and relevant observations of each one species are included.